Evaluation of Water Resources Development and Utilization in Liaoning Province Based on BP Neural Network - LIU Yang (Renmin Zhujiang)
This paper applies the BP neural network algorithm to the evaluation of water resources development and utilization in Liaoning Province,establishes the evaluation model of water resources development and utilization in Liaoning Province,and verifies the feasibility of the model by the AHP-entropy weight method-fuzzy comprehensive evaluation method.The traditional evaluation method of water resources development and utilization mostly depends on the determination of weight,resulting in increasing subjectivity and complexity of evaluation.While the BP neural network algorithm can identify the complex evaluation system well,which is accurate and fast.The results show that:Dandong and Fushun in the east of Liaoning are V3,with great potential for water resources development and utilization.Fuxin and Chaoyang in the west of Liaoning are V1,with small potential for water resources development and utilization.The other 10 cities are all V2,and the development and utilization of water resources is in the transitional stage,with certain potential.